2014
DOI: 10.1007/s11356-014-3662-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities of 48 pharmaceuticals and their freshwater and marine environmental assessment in northwestern France

Abstract: A risk assessment for freshwater and marine ecosystems is presented for 48 pharmaceutical compounds, belonging to 16 therapeutic classes, and prescribed in northwestern France. Ecotoxicity data were obtained on two freshwater organisms, i.e., crustacean Daphnia magna and the green algae Pseudokirchneriella subcapitata, and on two marine organisms, i.e., the crustacean Artemia salina and the diatom Skeletonema marinoi. Measured environmental concentrations (MEC), in the Orne River and sea off Merville-Francevil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(90 citation statements)
references
References 26 publications
8
65
1
2
Order By: Relevance
“…Although there are no ecotoxicological studies using dexketoprofen, there are a few studies in the literature reporting the exposure of P. subcapitata to racemic ketoprofen. These studies reported different EC50 values, with the lowest being 4 mg/L [40] to 24.6 mg/L and the highest being 49.3 mg/L [41,42]. The present study showed an EC50 value in P. subcapitata exposed for 96 h to racemic ketoprofen that is 16.7fold lower than the lowest value reported in the literature.…”
Section: Ecotoxicological Assessmentcontrasting
confidence: 77%
See 1 more Smart Citation
“…Although there are no ecotoxicological studies using dexketoprofen, there are a few studies in the literature reporting the exposure of P. subcapitata to racemic ketoprofen. These studies reported different EC50 values, with the lowest being 4 mg/L [40] to 24.6 mg/L and the highest being 49.3 mg/L [41,42]. The present study showed an EC50 value in P. subcapitata exposed for 96 h to racemic ketoprofen that is 16.7fold lower than the lowest value reported in the literature.…”
Section: Ecotoxicological Assessmentcontrasting
confidence: 77%
“…These studies reported different EC50 values, with the lowest being 4 mg/L [40] to 24.6 mg/L and the highest being 49.3 mg/L [41,42]. The calculated EC10 values for both racemic ketoprofen and dexketoprofen were comparable to the observed NOEC values for both pharmaceuticals.…”
Section: Ecotoxicological Assessmentmentioning
confidence: 60%
“…In a few cases, such as the green alga Pseudokirchneriella subcapitata , the duckweed Lemna gibba , or the African clawed frog Xenopus laevis , more than 1 NOEC was located; these were geometrically averaged (Table ). Two NOECs, for P. subcapitata and Skeletonema marinoi , were kindly made available by L. Minguez (Université de Caen Basse‐Normandie, France, personal communication) . In total, 16 different endpoints span a wide systematic range, including cyanobacteria over various groups of algae, flowering plants, 3 groups of invertebrates, and vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmaceuticals are a large synthetic or natural group of substances that represent a several set of biologically active molecules designed to treating, curing and preventing diseases, thus improving the human and animal health (MINGUEZ et al, 2016;CAI et al, 2017). Among the classes that constitute the pharmaceutical group, highlight the anti-inflammatory, antibiotics, analgesics, lipid regulators, antidepressants, chemotherapy agents, contrasts, beta blockers and hormones.…”
Section: Introductionmentioning
confidence: 99%